Framing Media Massa Dalam Pilgub Jabar - Budi Prayitno (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2013)
Faucets democracy that is currently underway has given a tremendous effect in many aspects, especially in the context of political and press freedom. These two aspects are very concerned when we noticed lately. However, the dynamics of the political parties have become food for the print and electronic media in any preaching. No exception is mass media attention in every event of political contestation at all levels, both at the provincial, district / city. Role of the press as a means of political communication to form a self image of the candidate is believed to bring sufficient influence on the preferences of voters in 26 districts/cities in West Java Province. This study aims to determine how the frame (framing) reporting by mainstream media outlets that the authors consider to have influence in the province of West Java. Media is used as an analytical tool is Mind and Sept tar Indonesia West Java edition. Both authors use this medium as an analysis of the material because it has a special column that reported the development of the West Java guvernour election.